Development and implementation of textile production planning system based on process control. (1st January 2013) - Dong, Yude; Sun, Qinqin; Wang, Xiuye; Zhang, Caixia; Yang, Bing; Li, Shengzhao
Taking a textile enterprise as the model, discussing its business process, a new textile production planning system is developed based on process control. Firstly, production status of the enterprise is analysed, and then design and control of the system process is introduced. Secondly, function of automatic production planning as well as loom monitoring and scheduling in the system are specially put forward to change the chaotic production planning, and then modular design for the system is analysed. At last, implementations of the production planning management module, the loom monitoring and scheduling module and the main interface are introduced, later on application effect of the system in the textile enterprise is summarised.